A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages Schools now sitting under the chairmanship of Sir William Goodenough. Meanwhile some general considerations of which account will be taken in devising the new service can be mentioned. There are not yet enough men and women of real consultant status and one of the aims will be to encourage more doctors of the right type to enter this branch of medicine or surgery and to provide the means for their training. There is also need for a more even distribution. The main consultant facilities are now inevitably concentrated at the medical teaching centres. The consultant service still needs to be organised with the teaching centre as its focus, but the service must be spread over a wider area by enabling and encouraging consultants taking part in it to live and work farther afield. Apart from greater accessibility to the public, this will also have a beneficial effect upon general medical practice over larger areas — where the habitual presence and services of consultants will serve as a means of continuing postgraduate education. The consultant taking part in the service must be associated with his particular hospital or hospitals on a much more regular basis — and with more regular attendances and duties — than is often the case now, when he is regarded as merely "on call." It will often be desirable that he should be associated with more than one major hospital, so that the sharing of a common consultant staff may become an effective link between hospitals. His normal function will be the regular and frequent visiting of these hospitals, both for in-patient and for out-patient consultation; also the visiting of outlying "general practitioner" hospitals, which need to be linked with the major hospitals ; also, for certain consultants as circumstances may require, the visiting of Health Centres and clinics and, in case of need, at the request of the general practitioner, of patients in their homes. For this sort of duty the proper and regular remuneration of consultants, through the hospitals with which they are associated, will become essential. This remuneration, and the engagements entered into in respect of it, can be on either a full-time or a part-time basis (and might well include part-time engagements with more than one hospital). The terms and conditions for these consultants will be a matter for the authorities of the hospitals, voluntary or municipal, which offer the appointments ; but in order to avoid anomalies as between hospital and hospital and between area and area some central regulation of remuneration will be required. There will also be need for some control over the discretion of individual hospital authorities in making appointments to senior clinical posts. Under existing practice there is a danger of "inbreeding"; and, while the ultimate responsibility for an appointment should rest unmistakably with the body of persons conducting the hospital's affairs, there is much to be said for a system under 17 36/H24/41